2020
DOI: 10.1007/s10067-020-05106-3
|View full text |Cite
|
Sign up to set email alerts
|

Can metabolic profiling provide a new description of osteoarthritis and enable a personalised medicine approach?

Abstract: Osteoarthritis (OA) is a multifactorial disease contributing to significant disability and economic burden in Western populations. The aetiology of OA remains poorly understood, but is thought to involve genetic, mechanical and environmental factors. Currently, the diagnosis of OA relies predominantly on clinical assessment and plain radiographic changes long after the disease has been initiated. Recent advances suggest that there are changes in joint fluid metabolites that are associated with OA development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Lipid molecules were found at T0 vs. T28 and T0 vs. T84. These possible biomarkers were related to the findings of several studies, where there is an alteration of lipid metabolism associated with OA due to its pro-inflammatory properties [22][23][24]39,40]. Kosinska et al detected alterations at the level of phospholipids and sphingolipids at different stages of the disease in synovial fluid [41][42][43].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Lipid molecules were found at T0 vs. T28 and T0 vs. T84. These possible biomarkers were related to the findings of several studies, where there is an alteration of lipid metabolism associated with OA due to its pro-inflammatory properties [22][23][24]39,40]. Kosinska et al detected alterations at the level of phospholipids and sphingolipids at different stages of the disease in synovial fluid [41][42][43].…”
Section: Discussionmentioning
confidence: 85%
“…For this reason, it has become an ideal method for the identification of OA biomarkers in a variety of biological samples. Different studies have reported several metabolites and metabolic pathways that can be altered in OA, such as amino acid metabolism, fatty acid and lipid metabolism, phospholipids, arginine, phosphatidylcholine, L-tryptophan, tyrosine, carnitine, and arachidonic acid [ 1 , 2 , 4 , 10 , 20 , 21 , 22 , 23 , 24 , 25 ]. In order to identify biomarkers, one must go to the metabolic pathways that affect amino acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Its clinical manifestations are the slow development of joint pain, stiffness, joint swelling, limited activity, and joint deformity. [26] The pathogenesis of OA is complex.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it has become an ideal method for the identification of OA biomarkers in a variety of biological samples. Different studies have reported several metabolites and metabolic pathways that can be altered in OA, such as amino acid metabolism, fatty acid and lipids metabolism, phospholipids, arginine, phosphatidylcholine, L-tryptophan, tyrosine, carnitine, and arachidonic acid [1,2,4,9,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%